2011
DOI: 10.1021/jp201386v
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Mixed Aromatic Counterions on Nanostructures and Drag Reducing Effectiveness of Aqueous Cationic Surfactant Solutions

Abstract: Drag reduction effectiveness of two dilute quaternary ammonium surfactant aqueous solutions with different pairs of mixed aromatic counterions was investigated along with their micellar nanostructures revealed by cryo-TEM imaging, zeta potential, particle size, and (1)H NMR measurements. Certain combinations of aromatic counterion mixtures showed significant synergistic effects. They dramatically improved drag reduction effectiveness relative to either single aromatic counterion. Using mixed aromatic counterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
(72 reference statements)
0
9
0
1
Order By: Relevance
“…Thus, cationic surfactants can have wide temperature ranges suitable for both district heating and cooling systems. The effects of mixed counterions were similar but less dramatic [11,172,176].…”
Section: Drag Reduction Of Cationic Surfactantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, cationic surfactants can have wide temperature ranges suitable for both district heating and cooling systems. The effects of mixed counterions were similar but less dramatic [11,172,176].…”
Section: Drag Reduction Of Cationic Surfactantsmentioning
confidence: 99%
“…Sodium salicylate is the most widely studied counterion. Chou et al [171, 174] found that an Ethoquad O-12/sodium salicylate solution at a molar ratio of 1.5 : 1 showed most effective drag reduction at 2°C. Excess quantities of sodium salicylate (0.2 wt.%) in the cetyl trimethyl ammonium salicylate (CTASal) system (0.2 wt.%) were observed by Rose et al [168, 170] to increase the critical Reynolds number (from about 20000 to about 50000) and the critical temperature (from 50°C to 70°C).…”
Section: Drag Reduction In Surfactant Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, nonionic surfactants have been proven to be effective for a limited range of temperatures and concentrations only [29][30][31]. Cationic surfactants performance as DRAs have been tested extensively by many researchers, especially when they are combined with a suitable counter-ion [32][33][34][35][36]15]. The presence of the counter-ion will help the cationic surfactants to form long rod-like micelles by dispersing the head group charge.…”
mentioning
confidence: 99%
“…З одного боку ПАР є аналітичними реагентами, а з іншого -здатні ефективно впливати на фізико-хімічні властивості інших речовин у розчинах. Відомо [2,3], що використання міцелярних систем дає можливість збільшити квантові виходи у 2-10 разів, інтенсивність флюоресценції в 3-80 разів, і, відповідно, знизити межі виявлення аналітів на 1-2 порядки. Організовані середовища на основі ПАР впливають на флюоресценцію люмінесцентних індикаторів та їх комплексних сполук завдяки зміні у міцелярному розчині їхніх фотофізичних характеристик, агрегатного стану та характеру мікрооточення [4,5].…”
Section: досліджено вплив поверхнево-активних речовин різних типів наunclassified